Chemical Factors in Clothes Wastewater Affect the Development of Aedes aegypti Mosquitoes - Ramayanti, Indri; Prameswarie, Thia; Ghiffari, Ahmad; Alpasyah, M. Mico (Majalah Kesehatan Indonesia, 2025)
Dengue hemorrhagic fever is caused in part by Aedes aegypti. Ae. aegypti's primary breeding habitat is a non-groundwater reservoir. Chemical variables including pH, salinity, Dissolved Oxygen (DO), and Total Dissolved Solids (TDS) all have an impact on the growth of Ae. aegypti larvae. The purpose of this study is to examine the effect of water chemistry parameters on egg hatchability as well as the number of Ae. aegypti larvae and pupae in clothes washing wastewater. The experimental design in this study was a Completely Randomized Design (CRD) with three treatment media (washing clothes wastewater from dengue patients' houses, water municipal waterworks, and abate) three repetitions. The parameters measured are egg hatchability, number of larvae, number of pupae, dissolved oxygen (DO), pH, salinity, and total dissolved solids. The data were analyzed using one-way ANOVA and the Honestly Significant Difference (BNJ) test at a 5% confidence level. The results showed that wastewater from washing clothing had a 26.00% affect on the hatchability of Ae. aegypti, 22.67% of the larvae, and 10.67% of the pupae. The chemical content in clothes washing wastewater for DO is 7.60 mg/L, TDS is 136.00 ppm, pH is 7.80, and salinity is 0.10%.  The chemical content of DO and TDS in clothes washing wastewater differs greatly from water municipal waterworks and abate water, while pH and salinity do not differ significantly. This study concludes that wastewater from washing clothes has the potential to serve as a breeding ground for the Ae. aegypti mosquito, which transmits the dengue virus.